Workshop Karya Tulis Ilmiah untuk Meningkatkan Kompetensi Menulis Mahasiswa Fakultas Vokasi Universitas Negeri Yogyakarta - Arya Yusuf; Siti Nursipa Wulida (Faculty of Engineering, Universitas Semarang, 2024)
Writing skills have not been mastered by many students in higher education. Writing can be a means of conveying ideas in a rational, critical, and effective manner. Students can express ideas in the form of academic writing, such as essays. Essays can make students think critically, logically, and systematically. The purpose of this activity is to provide training in academic essay writing to new students of the 2023 Vocational Faculty of Yogyakarta State University. This activity is conducted online through lecture and discussion methods. The service team comes from the Research Student Activity Unit of the Vocational Faculty of Yogyakarta State University. Several participants asked questions and were enthusiastic about expressing their ideas. This training is considered successful and smooth, receiving positive responses from the participants. This training has helped vocational students at Yogyakarta State University to understand the rules of essay writing and to increase student's interest and enthusiasm in generating creative and innovative ideas.